Microbial Signatures of Pediatric Disease: Investigating the Gut Microbiome in Asthma and Eczema - Nasir, Faseeha; Gul, Sarooj (Indus Journal of Bioscience Research, 2025)
Pediatric asthma and eczema are prevalent chronic inflammatory conditions with significant health impacts globally. Recent research highlights the gut microbiome’s pivotal role in immune system development and allergic disease pathogenesis via the gut–skin–lung axis. This cross-sectional study investigated gut microbial signatures in 180 Pakistani children aged 1–12 years, including those diagnosed with asthma (n=60), eczema (n=60), and healthy controls (n=60). Using 16S rRNA gene sequencing, we analyzed gut microbial diversity and composition. Children with asthma and eczema exhibited significantly reduced microbial alpha diversity compared to controls (Shannon index: asthma 2.9, eczema 3.0 vs. controls 3.5, p < 0.001). Asthmatic children showed increased Proteobacteria and decreased Bacteroidetes, whereas eczema cases demonstrated elevated Firmicutes, including Clostridium sensu stricto and Staphylococcus aureus. Notably, Faecalibacterium prausnitzii, an anti-inflammatory butyrate producer, was markedly depleted in both disease groups. Multivariate analyses confirmed low F. prausnitzii abundance as independently associated with asthma and eczema. These findings underscore significant gut dysbiosis linked to pediatric allergic diseases in a low-middle income setting, highlighting potential microbial targets for therapeutic modulation. Further longitudinal and functional studies are warranted to explore causality and intervention strategies, which could pave the way for microbiome-based prevention and treatment in childhood asthma and eczema.